Citizen Journalism Influence on Mainstream Media in Reporting the Kanjuruhan Stadium Tragedy - Dumadi, Dhinar Arga; Ferdiani, Kabrina Rian (Universitas Gadjah Mada, 2025)
After the Kanjuruhan Stadium tragedy—riots after League 1 match between Arema FC and Persebayafootball teams at Kanjuruhan Stadium, Malang, East Javahappened,multiple information of citizen journalism appeared on social media. This article aims to determine the accountability and influence of citizen journalism on the reporting of mainstream media dealing with the Kanjuruhan Stadium tragedy on the period between October 1 to 11, 2022. The method applied in this research is a case study with a qualitative approach. Data are collected using observation and documentation techniques from online mainstream media—which is news article—or even offline one—that is character generic in news broadcasts of television station. Meanwhile, data related to citizen journalism dealing with the tragedy are gained from social media. In conclusion, it is proven that information from citizen journalism contributes a major influence to the direction and headlines of mainstream mass media, even though not all of the information is reliable. Initially, mainstream mass media reports such as detik.com, kompas.com, tvOne, Metro TV and Kompas TV tended to blame Arema FC supporters a.k.a Aremania. The focus of the mainstream mass media reporting was Aremania’s anarchic action regarding their favourite team—Arema FC—lost the match against Persebaya. Based on the point of view of the report, the shooting of lachrymatory gas was considered normal due to the out of control chaos happened. Anyhow, not until a day, did the perspective of mainstream mass media reports reverse. It happened due to the emergence of citizen journalism as Twitter tweets, voice recordings, videos and photos on social media. Mainstream mass media then wrapped the reports of Kanjuruhan Stadium tragedy as horrors experienced by Aremaniain the tragedy. The authorities were blamed on these reports. They were figured as abusive party because they fired lachrymatory gas hastily to the supporters.